2014
DOI: 10.1176/appi.ps.201300455
|View full text |Cite
|
Sign up to set email alerts
|

Foster Care, Externalizing Disorders, and Antipsychotic Use Among Medicaid-Enrolled Youths

Abstract: Objectives The authors investigated the extent to which clinical externalizing disorder diagnoses explain increased rates of antipsychotic use in foster youth. Methods Medicaid claims data from 44 states for 2009 were analyzed to determine antipsychotic use rates among foster youth (n=301,894) and non-foster youth (n=5,092,574), excluding individuals diagnosed with schizophrenia, bipolar, autistic, or major depressive disorder. Logistic regressions assessed the relationship among foster status, externalizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 12 publications
0
21
1
Order By: Relevance
“…The use in privately insured youth has been more modest, with a steady increase across 11 years from 0.21% in 1996 to 0.90% in 2006 . In addition, numerous survey and administrative claims data have revealed that the majority of youth treated with antipsychotics were diagnosed with BD. Within Medicaid programs, antipsychotic treatment was particularly common in youth who were in foster care .…”
Section: Discussionmentioning
confidence: 99%
“…The use in privately insured youth has been more modest, with a steady increase across 11 years from 0.21% in 1996 to 0.90% in 2006 . In addition, numerous survey and administrative claims data have revealed that the majority of youth treated with antipsychotics were diagnosed with BD. Within Medicaid programs, antipsychotic treatment was particularly common in youth who were in foster care .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed that many adopted children have previous chronic illnesses or are at risk for the development of physical and mental health issues. 26,[64][65][66][67][68][69][70][71] In 2014, a report from the Congressional Research Service found that 35% to 60% of children in the child welfare system had at least 1 chronic or acute physical health condition that needed treatment. 64 Some of the most common findings were growth failure, asthma, obesity, vision impairment, hearing loss, neurologic problems, sexually transmitted infections, and complex chronic illnesses.…”
Section: Chronic Health Concernsmentioning
confidence: 99%
“…26 These children are more likely to report externalizing and internalizing psychiatric symptoms. [65][66][67][68][69] The pediatrician plays a key role in coordinating the health care management of adopted children with special health care needs. After any acute and chronic illnesses have been identified, a review of any previous medical testing is appropriate to make referrals to pediatric medical subspecialists.…”
Section: Chronic Health Concernsmentioning
confidence: 99%
“…Another example is ADHD, which is diagnosed and treated in a bimodal way, with poor children on Medicaid getting second‐generation antipsychotics to tranquilize their “behavioral problems” (Vanderwerker et al. ) and affluent children getting stimulants to enhance their academic performance (Yallop et al. ).…”
Section: “Integration” Of Psychiatry With Medicine As An Agent Of Segmentioning
confidence: 99%
“…For example, what I came to see in buprenorphine was the flip side of pharmaceuticalization of poverty; it is the pharmaceuticalization of affluence. Another example is ADHD, which is diagnosed and treated in a bimodal way, with poor children on Medicaid getting second-generation antipsychotics to tranquilize their "behavioral problems" (Vanderwerker et al 2014) and affluent children getting stimulants to enhance their academic performance (Yallop et al 2015). Psychotropic drugs are shaping class and race at both ends, through the moral actions of psychiatrists with both affluent white patients who pursue social advantages through medicalization of their behavior and with low-income nonwhite patients who lose moral agency through medically authoritative designations that they are irredeemable.…”
Section: "Integration" Of Psychiatry With Medicine As An Agent Of Segmentioning
confidence: 99%